Bosnia and Herzegovina : 2010 Article IV Consultation Second and Third Reviews Under the Stand-By Arrangement Request for Waiver of Nonobservance of a Performance Criterion and Rephasing of Purchases. (IMF Staff Country Reports; Country Report ;, 2010)
The global economic and financial crisis found the economy of Bosnia and Herzegovina in a vulnerable position. The government put together a comprehensive program supported by the International Monetary Fund. The stabilization program has helped mitigate the impact of the global financial crisis on the economy. With the economy now emerging out of the recession, policy continuity is important. Medium-term fiscal consolidation should be accompanied by reforms in current spending while making room for capital expenditure. The response in the financial sector has been appropriate.